Solar energy engineering : processes and systems - Kalogirou, Soteris (Academic Press, 2014)
This edition includes revised and updated chapters on all areas of solar energy engineering from the fundamentals to the highest level of current research. Topics include: solar collectors, solar water heating, solar space heating and cooling, industrial process heat, solar desalination, photovoltaic technology, solar thermal power systems, modeling of solar energy systems and includes a new chapter on wind energy systems. As solar energy's vast potential environmental and socioeconomic benefits are broadly recognized, this book will provide professionals and students with a resource on the basic principles and applications of solar energy systems and processes and can be used as a reference guide to practicing engineers who want to understand how solar systems operate and how to design the systems. --